2004
DOI: 10.1177/0895904803262146
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of State Policies and Actions on Local Implementation Efforts: A Study of Whole School Reform in New Jersey

Abstract: This article integrates the technical model of policy implementation with a coconstructed perspective of implementation to understand the impact of the New Jersey Department of Education’s (NJDOE) actions and policies on implementation of a set of court-ordered mandates in 30 of the state’s poorest school districts (referred to as the Abbott or special needs districts). The analysis reveals that the organizational responses of the NJDOE subverted the goals of the reforms. At the same time, local districts have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Other structural characteristics, such as grade level and community poverty, have an indirect effect through certain school climate factors, such as organizational capacity and principal support (Payne et al 2006;Payne 2009). Even district and state policies have been shown to affect programs, serving to both insulate and isolate school reform in various ways (Boerm et al 2007;Bosworth et al 1999;Walker 2004).…”
Section: School and Community Structural Factorsmentioning
confidence: 98%
“…Other structural characteristics, such as grade level and community poverty, have an indirect effect through certain school climate factors, such as organizational capacity and principal support (Payne et al 2006;Payne 2009). Even district and state policies have been shown to affect programs, serving to both insulate and isolate school reform in various ways (Boerm et al 2007;Bosworth et al 1999;Walker 2004).…”
Section: School and Community Structural Factorsmentioning
confidence: 98%
“…There might be greater scope to affect the returns to human capital at the local level, however, where regional assistance policies can encourage investment in new high-technology ventures which employ and train workers and hence yield extra returns from their human capital (Aitken, Harrison, and Lipsey, 1996;Lipsey and Sjöholm, 2004). And there is often scope for local initiatives to improve the quality of human capital and its relevance to employers (Ferrer, 2000;Carnau, 2004) and to implement national policies with a regional flavor (Spillane, 1999;Walker, 2004).…”
Section: Policy Implicationsmentioning
confidence: 99%
“…In addition, Payne et al (2006) found that school size and urbanicity influenced quality of implementation, while other characteristics, such as the poverty level, had an indirect effect through certain school characteristics, such as organizational capacity and support. Finally, even district and state policies have been shown to affect program implementation Bosworth et al 1999;Walker 2004).…”
mentioning
confidence: 97%